2022
DOI: 10.1371/journal.pone.0264701
|View full text |Cite
|
Sign up to set email alerts
|

Modelling aptamers with nucleic acid mimics (NAM): From sequence to three-dimensional docking

Abstract: Aptamers are single-stranded oligonucleotides, formerly evolved by Systematic Evolution of Ligands by EXponential enrichment (SELEX), that fold into functional three-dimensional structures. Such conformation is crucial for aptamers’ ability to bind to a target with high affinity and specificity. Unnatural nucleotides have been used to develop nucleic acid mimic (NAM) aptamers with increased performance, such as biological stability. Prior knowledge of aptamer-target interactions is critical for applying post-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Computational modeling of aptamer tertiary structures and molecular docking are available in silico methods to help elucidate DNA aptamer–small-molecule interactions. Different workflows have been reported to model DNA oligonucleotides with different levels of accuracy compared to their characterized tertiary structure. Generally, they involve the generation of an RNA three-dimensional (3D) model that is later mutated to DNA and subjected to energy minimization prior to molecular docking analysis. The approaches based on 3D prediction tools and servers, albeit computationally inexpensive and straightforward, output the most probable RNA conformation, that is, the most thermodynamically stable conformation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational modeling of aptamer tertiary structures and molecular docking are available in silico methods to help elucidate DNA aptamer–small-molecule interactions. Different workflows have been reported to model DNA oligonucleotides with different levels of accuracy compared to their characterized tertiary structure. Generally, they involve the generation of an RNA three-dimensional (3D) model that is later mutated to DNA and subjected to energy minimization prior to molecular docking analysis. The approaches based on 3D prediction tools and servers, albeit computationally inexpensive and straightforward, output the most probable RNA conformation, that is, the most thermodynamically stable conformation.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches based on 3D prediction tools and servers, albeit computationally inexpensive and straightforward, output the most probable RNA conformation, that is, the most thermodynamically stable conformation. Nevertheless, it is known that the most thermodynamically stable unbound aptamer conformation (apo state) is not necessarily the most favorable for binding (holo state) . Additionally, these methods assume that there is only one unbound conformation; when in reality, an unbound aptamer is an ensemble of metastable states that coexist in a system. Therefore, accurate prediction of aptamer binding sites remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the identification of key interaction residues and structural motifs is helpful for aptamer design modification ( Sharma et al, 2017 ). Actually, few in silico example are reported that determine the three-dimensional conformation of aptamers and the binding to their target ( Oliveira et al, 2022 ).…”
Section: Oligonucleotide Therapies Recent Advancesmentioning
confidence: 99%
“…Development of specific and sensitive diagnostic tests is therefore imperative for appropriate patient management and treatment. Using aptamers selected against Leptospira from in vitro experiments, we derived their secondary and tertiary structures by adopting a previously described workflow for structural modeling [ 13 ]. Aptamer interactions with selected proteins were also predicted to determine possible binding residues.…”
Section: Introductionmentioning
confidence: 99%